RELASI PEMIMPIN INTEGRATIF: WACANA TEMATIK INTEGRASI SOSIAL DAN MANAJEMEN - Muhamad Husni; Muhammad Hasyim (CENDEKIA: Jurnal Studi Keislaman, 2018)
leader is the central and determinant of the success of the goals of the organization or institution, the leader must have high morality and integrity. morality and integrity are urgent things not only for the success of leaders and institutions or organizations they lead but also an attitude of upholding human dignity and respect for human rights as basic human rights that must be respected and developed Leaders are required to have the ability to create situations conducive, safe and comfortable for his subordinates so that his subordinates can carry out their duties well and discipline and optimally. Based on this, the problems that will be examined in this study lead to: how is integrative leadership in improving and developing organizational effectiveness how is the integrative leadership model in an organization.